A One Health approach to pastoral (im)mobility, health, and disease: A qualitative participatory study in Plateau State, Nigeria. - Dorien Hanneke Braam; Muhammad-Bashir Bolajoko; Charlotte C Hammer (PLOS Global Public Health, 2024)
In Plateau State, pastoralism has historically been a cost effective and resilient economic system well-suited to the ecological context. However, changes in land use and conflict have increasingly changed patterns of mobility. Pastoralist movement is now often associated with zoonotic disease transmission, environmental degradation and conflict, increasingly resulting in forced sedentarisation. Rather than a direct outcome of population movement however, animal, human and zoonotic disease drivers are complex and influenced by a range of socio-economic and environmental factors. The interlinkages of (im)mobility and health requires better understanding of underlying vulnerabilities to disease, which we aim to address in this study. Using a multisite case study methodology we investigated pastoralists' animal and human health concerns and priorities in Plateau State, Nigeria. We deployed participatory tools, including open-ended Focus Group Discussions, transect walks, mapping exercises, calendars and matrices. Data were analysed using a One Health conceptual framework. We interviewed 105 participants, from transhumance, migratory and sedentary households, dependent on livestock and small-scale crops. While transhumance was often preferred, participants had become sedentary as a result of insecurity, loss in livestock, and household characteristics. Humans and animals suffered from several endemic diseases, including zoonoses, however veterinary and human health services are only available in larger towns, and people mostly rely on community (animal) health workers and self-medication. Both transhumance and sedentary livestock keepers face challenges around forage grazing, regularly blocked by landowners, sometimes escalating into conflict. While conflict and changes in land use affected animal and human disease patterns, underlying political, social and economic risk factors were important determinants of health. There is a need for more inclusive, transdisciplinary, multilevel approaches to address animal and human disease, based on better contextualization of the challenges, through the participation of affected communities.